A study of 100 cases of arrthymia in first 48 hours of acute myocardial infarction - Panchotiya, Dushyant; Sadatiya, Mayur (International Journal of Research in Medical Sciences, 2023)
Background: Heart is the principle source of inspiration and focus among lovers and lyricists. Despite impressive strides in diagnosis and management, over last three decades’ acute myocardial infarction (AMI) continues to be a major public health problem in developing and developed countries. Cardiac arrhythmias directly and indirectly affect the morbidity and mortality of the patient with myocardial infarction and they are also related to in hospital and late mortality. Aims and objectives were to study the incidence of cardiac arrhythmias in AMI and the influence of various risk factors. Methods: A cross sectional observational study was conducted among total 100 patients of acute myocardial infarction with arrhythmia within 48 hours of symptom onset, during May 2018 to October 2019. Results: In our study, among 100 cases studied maximum incidence was in six decades of around 46%. Complications like left ventricular dysfunction and cardiogenic shock are more common with anterior wall infarction combined with inferior wall infarction. Most common risk factor observed was sedentary life style (72%), smoking (48%), IHD (38%), diabetes mellitus and obesity (34%). Mortality rate is 42.86% in complete heart block followed by 33.33 in second degree A-V block type 2. Conclusions: Myocardial infarction with arrhythmia was most common in sixth decade (46%) and male to female ratio is 3.35:1. Chest pain (96%), dyspnoea (54%), perspiration (59%), nausea and vomiting (43%) and palpitations (16%) were also present which should be kept in mind. Most common arrhythmia observed was premature beats and VPC's were more common (37%).